Which Pedagogical Parameters Predict the General Quality of ICT Integration from the Perspective of Elementary School Leaders?. Issue 3 (3rd July 2017) - Shamir-Inbal, Tamar; Blau, Ina
ABSTRACT: Technological changes in the digital age require schools to integrate innovative technologies in learning and the curriculum. This study analyzes data collected from elementary schools toward the end of the second and the third years of the national program for the gradual integration of ICT in Israeli schools. The study examines how school principals and ICT coordinators assess the systemic changes that have occurred in their schools. The parameters explored were collaboration (intraschool vs. interschool collaboration), digital content (using vs. designing digital content), and e-communication (within the teaching staff vs. between staff and families). An online questionnaire was distributed to the entire district of the Ministry of Education. The analysis was carried out on a total of 358 schools. Regression analysis showed that intraschool collaboration, digital content use and design, pedagogical update of class websites, and e-communication within the teaching staff explained 47.7% of variance in the general quality of ICT integration. It seems that school ICT leaders assess the general quality of ICT integration according to internal factors—in terms of collaboration within their schools and online interactions with colleagues—rather than external factors—collaborative activities between schools or e-communication with students and parents.